The Influence of Face Loss on Impulse Buying: An Experimental Study - Sun, Gong; Han, Xue; Wang, Hanwei; Li, Jie; Wang, Wangshuai (Frontiers in Psychology, 2021)
In this research, the effect of face loss on impulsive buying is examined under the background of Chinese culture. Using experimental studies, we examined the mediating effect of emotion and the moderating effect of self-control. The results indicate that individuals who lost their face are more likely to purchase impulsively. For individuals high in self-control, face loss has no significant impact on their impulsive consumption. While for those with low self-control, face loss will significantly enhance their impulsive buying tendency. Finally, implications, limitations, and directions for future research are discussed.